Rising China Power and Reassurance - Huisken, Ron (ANU Press, 2009)
Asia looks and feels very different now compared to the days of the Cold War. The sense that Asia now works differently can be traced to a single source - the re-emergence of China. China was the dominant power in greater Asia for most of recorded history. This historical norm was interrupted from the early 19th century, too far into the past to be recognisable and readily accommodated by the actors in today's international arena. A powerful China feels new and unfamiliar. Arriving peacefully at mutually acceptable relationships of power and influence that are very different from those that have prevailed for the past half century will be a demanding process. The world's track record on challenges of this kind is not terrific. It will call for statesmanship of a consistently high order from all the major players, and building the strongest possible confidence among these players that there are no hidden agendas.